(untitled) (Ustozlar uchun, 2024)
Abstract: The Finnish education system is based on the autonomy and selfdetermination of teachers. Teachers are owners of their teaching, and students are owners of their learning. Both are self-guided through the syllabus. As to education in Uzbekistan, in both public and private universities, the classroom management style (including the administration of schools) is authoritarian, where students and teachers have no say in their own management, and they are seen to need explanations. Lack of self-determination and autonomy, i.e., owning your learning and teaching, creates a negative self-development experience that forces the administration to step up more controls on both teachers and students, resulting in lack of trust, collaboration, ownership, and autonomy.